Psychological Needs, Goal Orientations and the Cultural Preferences of Individuals with Start-up Aspirations - Taggar, Simon; Kay, Michael (Senate Hall, 2018)
The present study examined individuals with start-up aspirations. The study objective was to test relationships between basic psychological needs and achievement goal orientation(s). The second objective was to test relationships between goal orientation(s) and preferred organizational culture. Our theoretical argument is that preferred culture is influenced by perceived person-environment fit. Preferred culture can therefore be partly understood by peoples' motives and goals. That is, people choosing self-employed will prefer an environment that fits their goal orientation and not everyone has the same goal orientation. Our findings suggest that basic psychological needs lead people to prefer certain organizational cultures. Goal orientations were mid-level mechanisms that mediated between psychological needs and business start-up preferences. We make recommendations based on understanding and changing goal orientations. Keywords: goal orientations, cultural preferences, self-employment aspirations
Keywords: goal orientations|cultural preferences|self-employment aspirations